The Valuation of Multiple Stock Warrants - Lim, Kian Guan (Institutional Knowledge at Singapore Management University, 2003)
The issue of multiple series of stock purchase warrants by the same firm is an interesting financial structure not just in America, but is common in countries such as Switzerland, Malaysia, and Singapore. This paper derives valuation formulas for multiple series of outstanding warrants. The theoretical warrant prices from this model are compared against existing models. We report a subtle slippage effect and also a cross dilution effect that cause the existing models, such as Galai-Schneller model, to be inappropriate for pricing such classes of multiple warrants. We also provide an example to illustrate the practicality of our model. The Greeks of the model are also derived in this paper. The complexity of multiple warrants could extend to other classes of contingent securities issued by the same firm but with differing expiry terms. [PUBLICATION ABSTRACT]